Examining personification in songs as one of the English teaching materials - Fata, Ika Apriani; Aprilya, Annisa (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
This research aims to figure out the types of personification used in one of the famous albums namely Michael Jackson's Thriller and Invincible. The sources of data were 19 songs taken from Thriller and Invincible albums by Michael Jackson and the lyrics of the songs. The research design used was descriptive qualitative research with documentation analysis as the technique of data collection. The result showed that there were 65 personification expressions found in the albums. Those 65 personifications were categorized into four types of personification as proposed by Dorst et al. (2011) namely: conventionalized personification (33 expressions), novel personification (20 expressions), default personification (12 expressions), and personification-with-metonymy (0 expressions). The idea of conventionalized personification presents in the lyrics is to dig out the beauty and tranquility of nature to life. It also might address giving an object or animal-human characteristics to create interesting imagery to the ELT Students. Also, these songs are assumed as one of the various English materials in language teaching in the future since it has no sarcasm and motivating contexts throughout the lyrics themselves.